Automated Attendance Monitoring System for primary schools / Ainul Azila Che Fauzi, Ahmad Aslam Yamani and Mohamad Syauqi Mohamad Arifin - Che Fauzi, Ainul Azila; Yamani, Ahmad Aslam; Mohamad Arifin, Mohamad Syauqi (Universiti Teknologi MARA, Kelantan, 2023)
For centuries, the practice of marking attendance has played a vital role in recording and monitoring the presence of sn1dems in educational institutions such as schools and colleges. In universities or institutions, it can be challenging to control students' attendance, particularly in large classes where their attendance is checked using a manual process which takes time and effort to identify or recall their faces. Automated Attendance Monitoring System for Primary Schools (AAMSPS) is developed to solve these issues. The principal aim of AAMS-PS is to create a web-based attendance recording system compatible with any device equipped with a web browser. This objective seeks to reduce reliance on paperwork, facilitating a more efficient and streamlined process for producing precise attendance results. The system focuses on providing a user-friendly interface to enhance usability. Furthermore, it enables the generation of efficient reports that cater to various requirements, such as viewing attendance on a yearly or monthly basis. This system is designed to benefit both teachers and administrators. It allows them to easily access and monitor attendance records based on specific dates or individual needs. Moreover, administrators have the flexibility to update sn1dent profiles and corresponding attendance records as required. In summary, the proposed solution addresses the challenges by offering a system that reduces paperwork, saves time, and ensures accurate attendance tracking.